Audience Rhetoric: Determinants of Interaction and Levels of Analysis - refice, belkheir (El Omda in Linguistics and Discourse Analysis, 2019)
Abstract; The eloquence of the public is one of the most recent topics, as researchers and scholars from various disciplines continue to present some procedural concepts or some methodological perceptions in order to make it a stand-alone science, or at least a branch of rhetoric or criticism. In this article we will attempt to address two fundamental issues: the first is the determinants of interaction; the second is the levels of analysis, and we hope to provide procedural work on how to study and define eloquence of the public